PERSEPSI KEMUDAHAN DAN PERSEPSI MANFAAT TEKNOLOGI INFORMASI MENJADIKAN GEN Z LEBIH BERANI BERPENDAPAT DALAM DUNIA MAYA - Harris, Ibnu; Dewi Kumalasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Universal., 2024)
The background to this research is that generation Z is a generation that is familiar with the use of digital and communication technology, such as social media, so it does not rule out the tendency for generation Z to become brand evangelists. This research contributes to extracting information in creating effective communication with Generation Z who are often considered to stutter in public, thereby further empowering them with appropriate technological interactions. The method used in this research is a quantitative approach with a total of 107 respondents from generation Z in Batam City. Respondents in this study were selected using a non-probability sampling method with purposive sampling technique. The research data were analyzed using Structural Equation Modeling (SEM) assisted by the IBM Amos version 26 application. The results of this research reveal that perceived usefulness influences the tendency of Generation Z in Batam City to become brand evangelists, while perceived ease of use has no influence.